Tindak Tutur Ilokusi Mama Dedeh (pada Program dari Hati ke Hati Bersama Mamah Dedeh di Stasiun Televisi Anteve) - Ningsih, Rika; Fatmawati; Wilda Srihastuty Handayani Piliang (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2021)
This study aims to analyze which illocutionary speech acts of Mama Dedeh are more prominent in the question-and-answer activity with the audience in the Dari Hati To Hati program with Mama Dedeh on Anteve television station in the Nikah Muda episode. This research has contained the dialogues in the session of questions and answers between the ustazah and the audience from the program Dari Hati To Hati Bersama Mama Dedeh. The results showed that Mama Dedeh only used three illocutionary speech acts out of Searle's five speech act classifications: representative, directive, and expressive. Of the three speech acts, the most dominant one used by Mama Dedeh is the representative speech act, which is 66.7%. Meanwhile, directive speech acts are only 22.2%, and expressive speech acts are only 11.1%.